Magnetic susceptibility of HCP iron and seismic anisotropy of the Earth’s core - Grechnev, G.E.; Ahuja, R.; Eriksson, O. (Физика и техника высоких давлений, 2003)
The seismic anisotropy of the Earth was proposed to be due to a preferred orientation of HCP iron crystals that constitutes the dominating element in the core. The suggested mechanism involves the anisotropy of the magnetic susceptibility χ of HCP iron, and it is argued that if χ is sufficiently anisotropic, a preferential orientation of the HCP crystals may occur. We have calculated ab initio χ and the anisotropy energy of HCP iron for pressures and temperatures corresponding to the Earth's inner core conditions. Our calculations demonstrate that χ is smaller when the field is along the c-axis of HCP iron. Hence, a toroidal magnetic field is shown to orient HCP Fe with c-axis along the north–south direction, and combined with the data on elastic constants this explains the seismic anisotropy.